Amplify-and-Forward Distributed Beamforming with Local CSI in the Presence of Interferences. (16th December 2015) - Kim, Jung-Bin; Choi, Ji-Woong; Choi, Hyuk; Cioffi, John M.
Abstract : This paper introduces an optimum amplify-and-forward (AF) distributed beamforming (DBF) in the presence of cochannel interference (CCI) when only local channel-state information (CSI) is available at each relay. It is shown that the proposed DBF closely achieves the performance obtained with global CSI when interference power toward relays is small or there are a large number of interferers but greatly reduces the complexity and overhead. The proposed DBF provides significant improvements over the conventional DBF designed without considering CCI at the cost of slightly increased complexity and overhead and achieves the capacity scaling of1 / 2 log ⁡ K throughK relays, where1 / 2 log ⁡ K corresponds to the maximal capacity scaling when there is no CCI.